BaslaWÍsh tálimde PánLer integraciyasÍ TiykarÍnda bilim sapasÍn arttÍrÍW - Nagmetova, N.M. (SCIENCE and SOCIETY, 2020)
The article describes the content of education in schools, methods of using integrated teaching in primary education, lesson plans in the current condition of integration tendency.